Ventajas e inconvenientes de la formación online - Marín Díaz, Verónica (2014)
The technological changes that society, in general, and,education in particular, have been experiencing demand that all levels of the education system be renovated. The emergencerenovation of a traditional education system such as distance education has become increasingly important each day if we take into account all the aspects involved in how people learn. elow we explain why we believe that online training, learning through networks or e-learning should be considered as a tool that provides a new way of seeing, feeling and understanding university education.